ENCAPSULATING PROPERTIES OF LEGUME PROTEINS: RECENT UPDATES & PERSPECTIVES. Issue 1 (1st January 2021) - Afzaal, Muhammad; Saeed, Farhan; Aamir, Muhammad; Usman, Ifrah; Ashfaq, Iqra; Ikram, Ali; Hussain, Muzzamal; Anjum, Faqir Muhammad; Waleed, Muhammad; Suleria, Hafiz
ABSTRACT: Encapsulation technology is gaining attention across the world owing to its promising protection of active ingredients under hostile conditions. Various wall materials are used in the encapsulation of these sensitive ingredients. However, the legume proteins (LPs) are emerging and unique carriers for the delivery of bioactive owed to their biocompatibility, film formation and functional attributes. Legume proteins loaded with active ingredients can be used for the development of various functional foods. Modification strategies are making the legume proteins effective wall materials against various hostile conditions for the protection of probiotics and other sensitive ingredients. The present review describes the promising potential of legumes for the protection of active ingredients. Additionally, the effect of various modification processes on the functional properties of legumes has been reviewed.